Should the patent system for pharmaceuticals be replaced? A theoretical approach. (October 2014) - Antoñanzas, Fernando; Rodríguez-Ibeas, Roberto; Juárez-Castelló, Carmelo A
<x xml:space="preserve">Abstract</x> This paper acknowledges the difficulties of providing access to innovative drugs in some jurisdictions under the patent system and it contributes to the current debate on mechanisms aimed at facilitating such access. We employ a highly stylized static model of two markets (North and South) to analyse the conditions under which a new system based on royalty payments would be preferred to a patent system for pharmaceuticals. In the welfare calculations we have considered explicitly the influence of marketing activities by the patent owner as well as the shadow price of public funds needed to finance the royalties. The bargaining power of the firm in terms of obtaining higher compensation is also considered. The result: are not unambiguously conclusive being heavily dependent on the relevant values of the parameters. Nevertheless, it seems that for realistic parameter values, the new system could be preferred by all the parties involved.